Unseen and unheard: cultural identities and the communicative repertoires of Índios in Brazilian cities. Issue 1 (1st January 2019) - Maher, Terezinha Machado; Cavalcanti, Marilda do Couto
ABSTRACT: The aim of this chapter is to take a critical and decolonial stance towards the experiences of Indigenous people in the urban diasporas of Brazil. We do this by discussing ethnographic data that provide insights into the impact of this migration on the construction of the identities of Indigenous Brazilians who move to urban spaces and consider how their cultural identities and communicative repertoires are represented. The data were collected during Indigenous teachers' educational courses carried out in the state of Acre, in western Amazonia between 1990 and 2010. We first draw attention to the ways that Brazilian society as a whole has difficulty acknowledging the presence of Indigenous peoples in our cities. We argue that, at the root of this invisibility, lies an essentialized concept of indigenous cultural identity that misplaces Indigenous peoples as prisoners of their ancestry and territoriality. We then demonstrate that these Indigenous citizens, when interacting with civil servants in urban centers, often see their legal rights disregarded, largely because their communicative repertoire and styles are negatively evaluated. Our argument is that, in order to try and reverse this situation, strongly decolonial language education policy and planning geared towards Brazilian public officials is needed.